Essays on the development of socioemotional skills - Fonseca, Gabriela do Couto (2020)
This thesis consists of three essays on applied microeconomics that discuss schools role on students’ socio-emotional development. All three essays use the same data source: a survey that took place in 2017 and 2018 in full-time primary schools in Rio de Janeiro. In the first chapter we contributed to the discussion of school’s role in socio-emotional learning by using data from a randomized control trial (RCT) with a longitudinal data from Programa Compasso (PC). Positive and significant results of the program were found on vocabulary and emotion recognition, especially for students of classes which completed at least 70% of PC lessons. We also found negative and significant results, associated with extensive exposure to the program, on working memory and bias towards recognizing negative emotions. In the second chapter our goal was to understand the role of teacher’s beliefs towards cognitive/non-cognitive skills on their task allocation and to also understand the impact of task allocation on students’ outcomes. We created an instrument to measure teacher’s teaching task allocation and their beliefs on the importance of cognitive/non-cognitive skills. We conducted a randomized control trial in which half of teachers received text messages about the importance of socioemotional skills. We are able to show that this intervention had a positive and significant effect on teacher’s belief, which lead teacher to increase their socioemotional investments in about 6%, in comparison to control teachers. Also, treatment had a direct positive impact on students’ socio-emotional skills. In the third chapter we seek to causally identify the effect that violence can have on the socio-emotional skills and well-being of students and teachers. For violence variable we used data from an open source application in which users georeferenced occurrence of shootings in the metropolitan region of Rio de Janeiro. We then used state violence control policies as possible instrumental variables for violence. We find negative and small, but robust effects of violence on students’ empathy. Also, more violence in the vicinity of the school is related to a greater bias of children in relation to angry emotion, children witnessing aggressive situations more often. We identified evidence that students from schools that were more exposed to violence ended up feeling better and safer at schools.